PENGARUH SENAM KEBUGARAN JASMANI 2012 TERHADAP PENINGKATAN KEBUGARAN JASMANI SISWA SMA INSHAFUDDIN BANDA ACEH - septi hariansyah (CV Abid Abadi Jaya, 2026)
This study aims to determine the effect of the 2012 Physical Fitness Gymnastics on improving the physical fitness of students at SMA Inshafuddin Banda Aceh. The study uses a quantitative approach with an experimental method and a one-group pretest–posttest design. The research sample consists of 26 students selected from the population of SMA Inshafuddin Banda Aceh students. The instrument used to measure physical fitness level is the Indonesian Physical Fitness Test (TKJI) for ages 16–19 years. The results show an improvement in students’ physical fitness after being given the 2012 Physical Fitness Gymnastics treatment. The mean physical fitness score in the pretest is 20.38 with a standard deviation of 2.32, while in the posttest it increases to 22.54 with a standard deviation of 1.78. The normality test using the Kolmogorov–Smirnov and Shapiro–Wilk tests shows that the data are normally distributed, with significance values greater than 0.05. Furthermore, the paired t-test results show a calculated t value of 13.170 with a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest results. Based on these findings, it can be concluded that the 2012 Physical Fitness Gymnastics has a significant effect on improving the physical fitness of students at SMA Inshafuddin Banda Aceh